Introduction. Palmyre-Tadmor : le patrimoine culturel en guerre - Sylvie Crogiez-Pétrequin (Les Cahiers d’EMAM)
The heritage of mankind, as defined by Unesco, is considered to be a common asset for all humanity, threatened by armed conflict, even if the dangers to archaeological and architectural heritage remain manifold. After its instrumentalization by the Syrian Baathist regime, the destruction by Daech of Palmyra’s archaeological heritage, perceived as a symbol of both Western civilization and the national identity of the Syrian state, is thus destined to shock Westerners, just as the use of Palmyra was envisaged by the Syrian state in the construction of the Syrian national novel.